Processes and mechanisms of welding residual stress and distortion - Feng, Zhili (Woodhead Publishing in materials., 2005)
Measurement techniques for characterisation of residual stress and distortion have improved significantly. More importantly the development and application of computational welding mechanics have been phenomenal. Through the collaboration of experts, this book provides a comprehensive treatment of the subject. It develops sufficient theoretical treatments on heat transfer, solid mechanics and materials behaviour that are essential for understanding and determining welding residual stress and distortion. It will outline the approach for computational analysis that engineers with sufficient back.